Ezra, Nehemiah - Williamson, Hugh Godfrey Maturin, 1947- (Waco, TX Word, 1985)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Ezra -- commentaries; Bible. O.T. Nehemiah -- commentaries